Determinant Factors of Working Children based on Conditional Logistics Regression for Matched Pairs Data: Determinan Anak Bekerja Berdasarkan Model Regresi Logistik Bersyarat untuk Data Berpasangan - Rizky Zulkarnain; Tri Listianingrum; Khairil Anwar Notodiputro (Indonesian Journal of Statistics and Applications, 2021)
Working children may create problem since it relates to human right as well as to the development of children especially in getting sufficient education. This paper discusses determinant factors of working children by using conditional logistics regression for matched pairs data. Matching is employed to adjust confounding factors and to avoid bias. In this paper there are three confounding factors that have been considered, i.e. residential area, gender, and income of household head. The results showed that the conditional regression model outperformed the standard regression model. The number of household members, whether the head of household was married or single, age of the head of household, educational attainment of the head of household, as well as the work status of the head of household were the determinant factors of the working children.